Pengembangan Usaha Mikro Kecil Menengah - Sartika Komalasari (CV. ITTC INDONESIA, 2025)
MSMEs have the ability to absorb a large workforce, distribute income more equitably, and support people-oriented economic growth. With their flexible, responsive nature and focus on local needs, MSMEs have great potential to grow into independent and sustainable economic forces. Despite these opportunities, MSMEs often face various obstacles, such as limited access to capital, low managerial skills, a lack of product innovation, and limited access to broader markets. In today's digital and globalized era, these challenges can hinder growth if not addressed with appropriate strategies and support from the government, the private sector, or empowerment institutions. Therefore, MSME development is crucial in efforts to improve community welfare and create an inclusive economy. This development process includes entrepreneurship training, access to capital, utilization of digital technology, strengthening institutions, and opening market access through intersectoral collaboration. It is hoped that these efforts will maintain MSME competitiveness, create new jobs, and strengthen the foundation of the national economy from the grassroots level. This research takes a descriptive exploratory approach to understand the opportunities and challenges in MSME development from various perspectives. This study was also developed through a literature review or desk study. The theoretical approach was conducted by referring to various sources, including books, academic journals, and the internet. All existing ideas were then combined into a single framework. With a population of approximately 255 million, technology is one of the main drivers of the Indonesian economy because it makes it easier for people to start businesses anywhere. The digital industry serves as a bridge to generate new entrepreneurs. Today, the proliferation of online marketplaces or online buying and selling platforms allows anyone, including mothers and young people, to sell food, clothing, or other handicrafts. A variety of products can be found on online sites. Large companies also actively sell their products online. Thus, the digital industry is a path to inclusive growth because strong internet penetration through smartphones allows more people to interact online, whether as producers, consumers, or trade intermediaries (APJII, 2016).